Validation of a food frequency questionnaire to determine vitamin D intakes using the method of triads. Issue 2 (7th August 2015) - Weir, R. R.; Carson, E. L.; Mulhern, M. S.; Laird, E.; Healy, M.; Pourshahidi, L. K.
Abstract: Background: Dietary sources of vitamin D (both natural and fortified) are increasingly contributing to consumers' vitamin D intake and status. Therefore, the present study aimed to validate a vitamin D food frequency questionnaire (FFQ) for the assessment of habitual vitamin D intake. Methods: A total of 49 apparently healthy consenting adults (aged 18–64 years) from the local community were sampled at the end of winter. Dietary intakes were recorded using a 4‐day weighed food record (4d‐WFR) and a 17‐item FFQ based on foods known to contribute to dietary vitamin D intake. Fasting vitamin D status was quantified by serum 25‐hydroxyvitamin D [25(OH)D] using liquid chromatography tandem mass spectrometry. The method of triads was applied using these three measurements to determine the overall validity of the FFQ. Results: Vitamin D intakes from 4d‐WFR ranged between 0.42 and 31.65 μg day −1, whereas intakes determined from the FFQ ranged from 1.03 to 36.08 μg day −1 . Serum 25(OH)D concentrations ranged between 12.89 and 279.00 nmol L −1 . The mean (SD) difference between the FFQ and 4d‐WFR was +1.62 ( 3.86). There were strong correlations between the vitamin D intake estimated by the FFQ and that from the 4d‐WFR ( r = 0.562) and also with serum 25(OH)D concentrations ( r = 0.567). Vitamin D intake estimated from the 4d‐WFR was also strongly correlated with serum 25(OH)D concentrations ( r = 0.411). The overall validity coefficient calculated using the method of triads was high (0.881). Conclusions: The vitamin D FFQ has been validated for use in future studies aiming to assess habitual vitamin D intake.